Potensi bakteri indigen Indonesia dalam mendegradasi karbofuran - Sopiah, Nida; Irawati, Wahyu; Wijaya, Yantra (Jurnal Biologi Udayana, 2022)
Pesticides play an important role in killing pests, both insects, fungi and weeds. The use of active-based pesticides in the environment can lead to the possibility of pollution. The use of carbofuran can cause pollution to soil, water, air, and also wildlife. Bioremediation is the right solution to overcome the problem of environmental pollution due to the use of pesticides. Bioremediation can be done by utilizing Indonesian indigenous bacterial isolates. This study aims to obtain information on the optimal growth of carbofuran-resistant bacterial isolates, the effect of adding various concentrations of carbofuran on the growth of bacterial isolates, and their ability to degrade carbofuran. Indigenous bacteria studied were isolates of carbofuran resistant bacteria from the Environmental Technology Center (PTL) collection. Bacterial growth was measured using a 600 nm wavelength spectrophotometer. The concentrations of carbofuran used were 100, 500, and 1000 ppm. Carbofuran degradation ability was measured using High Performance Liquid Chromatography (HPLC). The results showed that the addition of various concentrations of carbofuran affected the growth of bacterial isolates by reducing cell density. The growth of isolates R2, BN5.2 and BN5.3 was best in a medium containing 500 ppm carbofuran, while the growth of isolates R1, R3.2, R3.3, BN2.3, BN5.1 and C was best in a medium containing 1000 ppm. Bacterial isolates R2 and R3.3 were able to degrade carbofuran by 68.47% and 66.68%, respectively, for 3 days.